2014
DOI: 10.1016/j.ieri.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Research on Effect of Spruce Sawdust with Added Starch on Flowability and Pelletization of the Material

Abstract: To verify the effect of added starch on flowability and pelletization of spruce sawdust, were prepared mixtures with addition of 0, 5, 10, 15 and 20 % (w/w) starch. The measured basic mechanical-physical properties of the individual mixtures have shown that starch improves flowability of the mixture (growing value of the ffc parameter), reduces impact of friction forces on the contact stainless material (reduced wall friction), thus reducing energy demands of the process as regards flow of the mixture through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…4). In comparison with spruce sawdust briquettes, which were prepared with 5-20% starch binder (Jezerska et al, 2014), the banana bunch charcoal briquettes and the banana peel charcoal briquettes have lower hardness (≥50 kg). This was explained by the fact that the banana bunch charcoal briquettes and banana peel charcoal briquettes contain pore spaces and gaps, which can reduce the pellet resistance to deformation.…”
Section: Hardness Of Charcoal Briquettesmentioning
confidence: 97%
See 2 more Smart Citations
“…4). In comparison with spruce sawdust briquettes, which were prepared with 5-20% starch binder (Jezerska et al, 2014), the banana bunch charcoal briquettes and the banana peel charcoal briquettes have lower hardness (≥50 kg). This was explained by the fact that the banana bunch charcoal briquettes and banana peel charcoal briquettes contain pore spaces and gaps, which can reduce the pellet resistance to deformation.…”
Section: Hardness Of Charcoal Briquettesmentioning
confidence: 97%
“…The mixtures have shown that clay improves plasticity and flowability of the mixtures. The flowability improvement provided by clay can be attributed to the fact that it reduces impact of friction forces on the contact male/female roller configuration in a roller press briquetter (Jezerska et al, 2014). The clay set through the loss of water, binding the banana peel charcoal and banana bunch charcoal into briquettes, which could be handled like ordinary lump charcoal in domestic stoves (Rousset et al, 2011).…”
Section: Charcoal Briquettes Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing of the moisture by drying in the amount of about 12 tons (12% of the total initial weight) is quite difficult process, too. Thus, two dry products with a different biological value and different costs are obtained as the output (Jezerska, Zajonca, et al, 2014).…”
Section: A Review Of Literaturementioning
confidence: 99%
“…The latest challenges in the sector of biomass pelleting are to enhance the quality attributes of the products obtained in terms of better handling, longer storage time, better combustion, etc. An answer to this challenge was found by introducing various additives in pelleting recipes to improve quality [2][3][4][5][6]. The paper presents a series of experimental researches conducted on pellets obtained with and without additives to determine the influence of additives on the quality of final products.…”
Section: Introductionmentioning
confidence: 99%